Property Management Systems And Hotel Employee Performance In South Sulawesi: The Mediating Role Of System Benefits - Kurnia Yusniar Rahman; Herry Rachmat Widjaja; Ilham Junaid; Muaz Azinuddin (Ministry of Tourism Republic of Indonesia, 2026)
The rapid digitalization of the hotel industry has accelerated the adoption of Property Management Systems (PMS), which promise to improve operational efficiency and service delivery. Despite this, many hotels have not been able to fully translate PMS effectiveness into improved employee performance because the practical benefits perceived by employees are often overlooked. Previous studies have largely emphasized the direct effects of information systems on performance, while less attention has been allocated to the underlying mechanisms explaining how PMS effectiveness contributes to employee work outcomes. Therefore, this study aims to examine the interrelationship between PMS effectiveness, system benefits, and employee performance quality, with particular focus on the mediating role of system benefits. Using a quantitative approach, data were collected from 170 guest service agents employed in star-rated hotels in South Sulawesi, Indonesia. These data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that PMS effectiveness has a significant positive effect on both system benefits and employee performance quality. More importantly, system benefits have been found to significantly mediate the relationship between PMS effectiveness and employee performance, indicating that the successful translation of technological effectiveness into work quality depends on the extent to which employees experience practical operational benefits from the system. Unlike previous hospitality technology studies, which have primarily examined direct relationships between information systems and employee outcomes, this study conceptualizes system benefits as a distinct operational mechanism through which PMS effectiveness translates into employee performance quality. This approach extends existing technology acceptance and information systems success perspectives by emphasizing employee-perceived operational value rather than system usage alone. In addition, this study provides empirical evidence from the underexplored context of developing tourism regions and mid-scale hotels, while offering practical implications for optimizing PMS implementation to enhance workforce productivity and service quality. Nevertheless, the findings should be interpreted with caution, because the study relies on self-reported cross-sectional data collected from guest service agents working in three-star and below hotels in South Sulawesi. This factor limits causal inference and generalizability.